A fatal case of COQ7‐associated primary coenzyme Q10 deficiency. Issue 1 (3rd April 2019) - Kwong, Anna K.‐Y.; Chiu, Annie T.‐G.; Tsang, Mandy H.‐Y.; Lun, Kin‐Shing; Rodenburg, Richard J. T.; Smeitink, Jan; Chung, Brian H.‐Y.; Fung, Cheuk‐Wing
Abstract: Background: Primary coenzyme Q10 (CoQ10 ) deficiencies are clinically and genetically heterogeneous group of disorders associated with defects of genes involved in the CoQ10 biosynthesis pathway. COQ7 ‐associated CoQ10 deficiency is very rare and only two cases have been reported. Methods and Results: We report a patient with encephalo‐myo‐nephro‐cardiopathy, persistent lactic acidosis, and basal ganglia lesions resulting in early infantile death. Using whole exome sequencing, we identified compound heterozygous variants in the COQ7 gene consisting of a deletion insertion resulting in frameshift [c.599_600delinsTAATGCATC, p.(Lys200Ilefs*56)] and a missense substitution [c.319C>T, p.(Arg107Trp), NM_016138.4]. Skin fibroblast studies showed decreased combined complex II + III activity and reduction in CoQ10 level. Conclusion: This third patient presenting with lethal encephalo‐myo‐nephro‐cardiopathy represents the severe end of this ultra‐rare mitochondrial disease caused by biallelic COQ7 mutations. The response to CoQ10 supplement is poor and alternative treatment strategies should be developed for a more effective management of this disorder.